The search for victims of enforced disappearance: how the human rights obligation to search can be sucessfully implemented - Schulz, Christiane (Information)
The International Convention for the Protection of All Persons from Enforced Disappearance obliges contracting State Parties to search for disappeared persons. An investigation has to be conducted into the location and circumstances of their disappearance and, in the event of their death, their remains identified and returned to their family. In many places, this search proves difficult in practice, and often the political will and/or the technical means for such a search are lacking. In such cases, international urgent actions can support those affected in the search for disappeared persons.